METASTATIC GESTATIONAL TROPHOBLASTIC NEOPLASIA PRESENTING WITH GASTROINTESTINAL HEMORRHAGE AT THE NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY – A RARE CASE REPORT (Tạp chí Y học Cộng đồng, 2026)
Background: Gastrointestinal metastasis of gestational trophoblastic neoplasia (GTN) is a rare complication and poses a direct threat to life.Case Presentation: A 53-year-old woman presented with persistent gastrointestinal bleeding due to small bowel intussusception. Serum β-hCG was markedly elevated at 392,406 IU/L. Histopathology and immunohistochemistry confirmed metastatic GTN with multi-organ involvement. The patient was treated initially with low-dose EP chemotherapy followed by EMA-CO chemotherapy, achieving good clinical response and rapid decline of β-hCG levels.Conclusion: Early β-hCG testing and immunohistochemistry are essential for diagnosis of metastatic lesions of unknown origin in women. Initial low-dose chemotherapy may safely control life-threatening complications in high-risk GTN patients.
Keywords: Gestational trophoblastic neoplasia, gastrointestinal bleeding, choriocarcinoma, β-hCG.